Incidence of Different Type of Lip Lines among Medical Students at Prayagraj - Kaul, A; Rai , RK; Singh , DK; Gupta, AK (Journal of Indian Academy of Forensic Medicine, 2024)
Despite other available methods of identification studies of lip lines is emerging as a reliable tool of personal identification. The lip surface contains numerous fine grooves distributed vertically and horizontally at different inclinations to give rise to different types of lip lines. Study of lip print is called Cheiloscopy. Present study has been done to observe incidence of types of lip lines in different quadrants of lips on 200 undergraduate medical students at Moti Lal Nehru Medical College, Prayagraj. Digital images of lip lines were taken with the help of a DSLR Camera and observed using Tsuchihashi classification system. Type 1 (complete vertical) was the most common variety of lip line observed followed by Type 1'> 4 >2>5 > 3 in males and Type 1' > 4 > 5 > 2 > 3 among female subjects in order of incidence. Type 1 and lines in a clockwise manner from upper right (UR), upper left (UL), lower left (LL) to lower right (LR) quadrant of lips. This Type 1' lip lines were found commonly on lower lip quadrants (LL > LR) while Type 4 and Type 5 lines on upper lip quadrants (UL > UR) in most of male and female subjects. Order of incidence of different lip lines in upper quadrants (UR and UL) was Type 4> 5>2>3> 1'> 1among male and Type 4 >5>2>1' > 3>1 among female subjects while on lower lip it was Type 1> 1'>2>3 >4>5 in male and Type 1>1' >2>5 >3>4 in female subjects.
Keywords: Lip lines; Identification; Cheiloscopy